Protective effects of N-acetylcysteine and S-adenosyl-Lmethionine against nephrotoxicity and immunotoxicity induced by ochratoxin A in rats - Alkhattabi, Nuha A.; Khalifa, Fares; Al Doghaither, Huda; Al-Ghafari, Ayat; Tarbiah, Nesrin I.; Sabban, Aliaa (International Journal of Health Sciences, 2024)
Objective: The present study was designed to investigate the nephroprotective and immunoprotective effects of S-adenosyl-L-methionine (SAMe) in comparison to N-acetylcysteine (NAC) against ochratoxin A (OTA) – intoxication. Methods: Forty-eight adult male Sprague–Dawley rats were categorized into four groups: Control; OTA intoxication (5 mg OTA/kg diet); OTA + NAC, rats received 200 mg NAC/day before feeding balanced diet contaminated with OTA; and (OTA SAMe). Rats received 200 mg SAMe/day dissolved in distilled water orally just before feeding a balanced diet contaminated with OTA. Results: OTA administration altered serum kidney function biomarkers. These effects were pronouncedly alleviated by treatment with NAC. Results revealed a correlation between OTA-induced immunotoxicity and the reduced white blood cell (WBC) count. Treatments with SAMe significantly improved the WBCs count and hemoglobin concentration. Conclusion: NAC and SAMe have a protective role against nephrotoxicity and immunotoxicity induced by continuous administration of OTA. NAC was more effective in reducing OTA nephrotoxicity, whereas SAMe was more potent than NAC in reducing OTA immunotoxicity.